Blockade Billy - King, Stephen, 1947- (Cemetery Dance Publications, 2010)
"Even the most die-hard baseball fans don't know the true story of William "Blockade Billy" Blakely. He may have been the greatest player the game has ever seen, but today no one remembers his name. He was the first--and only--player to have his existence completely removed from the record books. Even his team is long forgotten, barely a footnote in the game's history. Every effort was made to erase any evidence that William Blakely played professional baseball, and with good reason. Blockade Billy had a secret darker than any pill or injection that might cause a scandal in sports today. His secret was much, much worse."